2014
DOI: 10.17221/510/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Quality of cows' milk from organic and conventional farming

Abstract: Kouřimská L., Legarová V., Panovská Z., Pánek J. (2014): Quality of cows' milk from organic and conventional farming. Czech J. Food Sci., 32: 398-405.The results of chemical and microbial analyses of raw milk samples coming from organic and conventional farming systems were statistically compared. The samples were analysed during a twelve-month period (June-May). A total of 2206 samples were collected of which 528 were organic. After raw milk was processed, sensory hedonic quality of 171 pairs of organic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 46 publications
4
22
2
Order By: Relevance
“…Only three studies reported significant (p<0.05) differences between conventional and organic. On conventional dairy farms compared to organic dairy farms, Kouřimská et al (2014) reported significantly lower (p<0.001) total mesophilic bacteria count in bulk milk and Čuboň et al (2008) mentioned significantly lower total bacteria count (p='++') and coliform organisms (p='+') in bulk milk, without giving a p-value. Kouřimská et al…”
Section: Dairy Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…Only three studies reported significant (p<0.05) differences between conventional and organic. On conventional dairy farms compared to organic dairy farms, Kouřimská et al (2014) reported significantly lower (p<0.001) total mesophilic bacteria count in bulk milk and Čuboň et al (2008) mentioned significantly lower total bacteria count (p='++') and coliform organisms (p='+') in bulk milk, without giving a p-value. Kouřimská et al…”
Section: Dairy Cattlementioning
confidence: 99%
“…The study of Čuboň et al (2008) involved only one organic and one conventional farm, the study of Coorevits et al (2008) only five farms each, and no number of farms was mentioned in Kouřimská et al (2014). These numbers in combination with the different hazards reviewed complicate extrapolation of the results to all dairy farms in the organic or conventional sector.…”
Section: Dairy Cattlementioning
confidence: 99%
“…In a study that was made in Ankara (Turkey) with milk collected from street mostly found S. aureus > E. coli > Klebsiella > Serratia > Proteus [67]. In a study conducted in Czech Republic, total amount of mesophilic bacteria-TMBC (×10 3 CFU/ml) in conventional milk was found as 19 ± 16 (as Mean ± SD; n:1168) and amount of coliform bacteria-CBC (×10 1 CFU/ml) was found as 48 ± 36 (as Mean ± SD; n: 473) [21]. In low input farms in Brazil, bulk milk bacteria count (BMBC) was found higher in winter 2174 ± 958.4 (Mean ± SEM) according to other seasons.…”
Section: Bacterial Contaminants In Conventional Animal Productsmentioning
confidence: 99%
“…According to the European Union (EU) Council Directive (EC 92/46/EEC) for the production of heat-treated drinking milk, plate count (30°C) for per ml of milk should be ≤100,000, somatic cell count-SSC for per ml of milk should be ≤400,000 in cows' milk and plate count (30°C) for per ml of milk should be ≤1,500,000 in goat's and sheep's milk [20]. In a comparative study, total mesophilic bacteria count-TMBC (×10 mesophilic n = 218; for coliform n = 101) were higher than conventional milk (for mesophilic n = 1168; for coliform n = 473) [21]. In one of the two different studies conducted in USA, no difference was present between organic and conventional (sum of grazing and not grazing) milk regarding SSC [22], and in the other study, very little difference was determined in terms of SSC and standard plate count [23].…”
Section: Introductionmentioning
confidence: 99%
“…The results of physical and chemical parameters obtained by various research groups have shown the difference between organic and conventional milk (Kouřimská et al, 2014, Shröder et al, 2011Kuhnen et al, 2015;Adler and Steinshamn, 2009;Butler et al,2008), as there absence (Petrov et al, 2016;Olivo et al, 2005;Croissant et al, 2007).…”
Section: Introductionmentioning
confidence: 99%